Between History and Theology—Zerubbabel and Nehemiah as Governors of Judah from the Perspective of Literary History - Schulz, Sarah (Religions, 2023)
Hag/Zech 1–8 and Ezr/Neh have in common that they are often rated as primary sources when it comes to the development of Second Temple Judaism(s). Consequently, it is mostly assumed that the Persian governors of Judah (like the Persian kings) significantly contributed to the (re-)formation of the Jewish community in Jerusalem after the exile: Zerubbabel built the temple, Nehemiah the wall of Jerusalem. As a rule of thumb, literary analysis within these books, if applied at all, is less critical than elsewhere in the Hebrew Bible. However, a literary critical approach gives rise to serious doubts about the historic reliability of these accounts. Based on a literary critical analysis of the relevant texts from Hag/Zech 1–8 and Neh, this article aims to show that it is only in the course of redaction history that the office of governor of Judah is ascribed to both individuals. Thus, the attribution of the office of governor to them reflects theological interests and concerns in the early Second Temple Period rather than the historical reality. As the texts not only attribute aspects of royal leadership to Zerubbabel and Nehemiah as governors of Judah, but also present the holders of a Persian office as custodians of Jewish interests (temple and Torah), it will be argued that the texts contribute to the political and religious reorganization of Judaism and, thus, to the formation of a collective Jewish identity.